2023
DOI: 10.1093/eurheartj/ehad117
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and cardiovascular outcomes in chimeric antigen receptor T-cell therapy recipients

Abstract: Aims Chimeric antigen receptor T-cell therapy (CAR-T) harnesses a patient’s immune system to target cancer. There are sparse existing data characterizing death outcomes after CAR-T-related cardiotoxicity. This study examines the association between CAR-T-related severe cardiovascular events (SCE) and mortality. Methods and results From a multi-centre registry of 202 patients receiving anti-CD19 CAR-T, covariates including sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The observation of substantial cardiovascular risks with BTEs adds to a growing body of evidence linking T-cell modulatory therapies with prognostic CVAEs. 17 27 In an analysis of patients treated with CAR-T therapy, CVAE development was the second-leading cause of death following therapy initiation. 17 Combined with our analysis, these observations suggest CVAEs following anticancer T-cell therapy are poorly tolerated and lead to reduced survival after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of substantial cardiovascular risks with BTEs adds to a growing body of evidence linking T-cell modulatory therapies with prognostic CVAEs. 17 27 In an analysis of patients treated with CAR-T therapy, CVAE development was the second-leading cause of death following therapy initiation. 17 Combined with our analysis, these observations suggest CVAEs following anticancer T-cell therapy are poorly tolerated and lead to reduced survival after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Having said that the high incidence of CTRCD observed in our study originates from the updated definition of CTRCD released by ESC [ 13 ], largely based on subclinical indexes like GLS and serum biomarkers, we believe that detecting such early manifestations might be important for improving CV outcomes in the cancer patient. A multicenter registry of 202 CART-cell patients receiving anti-CD19 therapies aimed at assessing a composite endpoint of heart failure, cardiogenic shock, or myocardial infarction [ 25 ]. Sixteen percent of subjects experienced severe cardiac events, which were independently associated with overall mortality (hazard ratio 2.8).…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen percent of subjects experienced severe cardiac events, which were independently associated with overall mortality (hazard ratio 2.8). In analyzing determinants of event occurrence the authors identified a role for CV risk factors, in particular hypertension and history of atrial fibrillation or heart failure; interestingly, however, there was no information on clinical usage of anti-IL6 medications to mitigate CRS in these patients [ 25 ]. Post-marketing analyses similarly showed a fatality rate of CV and pulmonary adverse events, including late-occurring cardiomyopathy, tachyarrhythmias, pleural and pericardial effusions, as high as 30.9% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in cardiovascular dysfunction are thought to be primarily mediated by the systemic inflammation of CRS, particularly IL-6. In a recent trial, CAR-T-related severe cardiovascular events were independently associated with increased non-relapse mortality and overall mortality risk [ 52 ]. ICU management is not specific, but cardiac MRI has emerged as an interesting tool for the diagnosis of CAR-T cell-related cardiotoxicity and differential diagnoses [ 53 , 54 ].…”
Section: Short-term Complicationsmentioning
confidence: 99%
“…ICU management is not specific, but cardiac MRI has emerged as an interesting tool for the diagnosis of CAR-T cell-related cardiotoxicity and differential diagnoses [ 53 , 54 ]. Because of the close interaction between CRS and CAR-T cell-related cardiotoxicity, cardiovascular complications must be managed with intravenous tocilizumab and are associated with rapid improvement [ 52 ] .…”
Section: Short-term Complicationsmentioning
confidence: 99%